Time to get re-organized! the structure of the Portuguese anti-austerity protests - Baumgarten, B. (2017)
Social movement research often focusses on phases of success and large protest events. By contrast, taking an interest in the question of how organizational change occurs within social movements, this study points out the importance of phases of low protest activity. The organizational structure of the Portuguese anti-austerity protests provides a thought-provoking case, as large protests organized by civil society actors other than the trade unions were a novelty in 2011. Furthermore, there are long periods of absence of large protests, and the organizational structure of the protests has undergone significant changes. Based on fieldwork in Portugal between September 2011 and March 2013, I differentiate between four phases in the organization of protests against austerity. I argue that it is mainly times of low degrees of activism – times that are rarely taken into account by social movement research – that lead to radical changes in the organizational structure of a social movement. The impact of the following factors on the direction of change is analyzed: (a) strategic choice; (b) values and normative commitments; (c) (potential) alliances and participants; (d) inspiration from other cases of social movement activism; and (e) learning processes, the history of social movements and the impact of memory.